A Strategic Review of the Security of European Countries - MAGIERA, Maciej; DONAJ, Łukasz (Przegląd Strategiczny, 2018)
This paper combines a review of the strategic security of European countries in 2017, and the creation – on the basis of the international scenario method – of short-, medium- and longterm forecasts. The authors address both the nature of armed conflicts (including the so-called ‘frozen conflicts’) and the escalation of terrorist acts. Also, the issue of the immigration crisis has been highlighted as causing both the rise of radical public sentiments and being a ‘source’ of the smuggling of people (including terrorists) and goods (including weapons which are later used in attacks).